*Caníbales por Cali van: Andrés Caicedo y el gótico tropical - Gómez, Felipe (Íkala, Revista de Lenguaje y Cultura, 2007)
Cannibalism and vampirism are recurring motifs in the films and fiction made by the Colombian interdisciplinary collective known as Grupo de Cali (the Cali Group). They are also fundamental for their aesthetic of the “Tropical Gothic”. Through this aesthetic, the Grupo effects a transcultural reappropriation and recreation of Gothic film and literature by incorporating the local parameters of youth in Cali during the 1960s and 1970s. In this article, I focus on representations of female cannibals found in fiction short stories by Andrés Caicedo, one of the founders of the Group, and I examine them using contemporary cultural theory and criticism related to the figures of Caliban and the cannibal in Latin America. Received: 10-04-07 / Accepted: 20-06-07 How to reference this article: Gómez, F. (2007). Caníbales por Cali van: Andrés Caicedo y el gótico tropical. Íkala, 12(1), pp. 121-141.